Differences in muscle power between the dominant and nondominant upper limbs of baseball players - Noguchi, T.; Demura, S.; Takahashi, K.; Demura, G.; Mori, Y. (The Journal of Strength and Conditioning Research, 2014)
We examined the differences in muscle power between the dominant and nondominant upper limbs of 33 healthy, right-handed, university baseball players (mean age, 20.4 ± 1.1 years) with an average baseball experience >11 years. After measuring maximal voluntary contraction (MVC) of hand grip, elbow flexion, and shoulder internal rotation in both upper limbs, the muscle power of each joint was measured at 40%, 50%, and 60% MVC. No significant differences were observed in the main factors affecting MVC and elbow flexion power loads between dominant and nondominant upper limbs. For handgrip power, load factors at 40% MVC in the dominant hand were lower than those at 60% MVC in the same hand and those at 50% and 60% MVC in the nondominant hand. Significant differences were observed in shoulder internal rotation power between dominant and nondominant upper limbs, with the dominant limb having greater power at all loads. Correlations between muscle power of both upper limbs for handgrip and elbow flexion were significant and moderately high at all loads. For shoulder internal rotation power, the degree of correlation was significant and moderately high at 40% MVC but low to moderate at 50% and 60% MVC. Therefore, baseball players have marked lateral dominance in shoulder internal rotation power unlike handgrip and elbow flexion power, although the relationship between shoulder internal rotation muscle powers of both upper limbs becomes lower with increasing load. The dominance of muscle power of each joint varied even in the same upper limb. It is thus beneficial for baseball players to train with even loads on both arms or adopt simultaneous workout of both arms after adjusting for strength differences.